Consommation indienne de vin en Nouvelle-Espagne au XVIe siècle : monopole, conflits politiques et projets coloniaux concurrents - Antoine Duranton (L'Atelier du CRH)
This article describes the political conflict rising from the establishment of the estanco de vino, a monopoly on wine aimed at controlling indigenous wine consumption in New Spain during the second half of the 16th century. Following the unsuccessful transplantation of grapevines in the viceroyalty, merchant networks imported and distributed this beverage, whose cultural dimension was of capital importance for Spanish identity. Having become an essential good of transatlantic trade, of major economic importance, wine was extensively drunk among Indigenous communities, which created a political crisis between the viceroys, at the origin of the ban, and the Audiencia of Mexico City, supported by the merchants. This conflict highlights two distinct colonial projects for New Spain. One was based on the evangelisation and the constitution of a Christian Indian republic while the second one was based on a civic ideal of establishing a virtuous and prosperous colony for its Spanish residents. This debate around the Hispanic drink illustrates the dividing lines within Spanish authority, at all levels of power